The Development of Spell Checker Android Application to Improve Students’ Pronunciation of English Education Department, IAIN Jember - Noviyanti, Sari Dewi (Department of English Language Education, UIN Sunan Ampel Surabaya, 2020)
Pronunciation and vocabulary are important elements of language so a communication will be difficult if the speaker cannot pronounce the elements or words accurately. However, in learning in class, limited time causes lecturers to have difficulty checking the pronunciation of English students one by one. So that technology is needed to improve students’ pronunciation competence independently and measurably. This study aims to develop a spell checker application that is integrated with the lecture module. This application aims to improve the English pronunciation ability of students independently and measurably so as to save time. The research method is a design and development method with 6 stages. The product validation results showed that this application is feasible to use with the acquisition of a feasibility percentage of 89%.